PENGGUNAAN BAHASA SLANG PADA AKUN AUTOBASE @COLLEGEMENFESS DI TWITTER PERIODE DESEMBER 2021 - FEBRUARI 2022 - Izzati Aulia Fikri; Ediwarman Ediwarman; Sundawati Tisnasari (Universitas Sultan Ageng Tirtayasa, 2023)
This research aim to describe the use and meaning of slang language in tweets on autobase account @collegemenfess that are send by the followers of the account. This research is a qualitative research with observising, documenting, and writing techniques as the methods. The instrument used in this research is the researcher herself or human instrument. Based on the r the data analysis that has been done, the researcher found 40 data on the use of slang language as follow (1) 15 abbreviations data; (2) 11 farcacical spellings data; (3) 10 shortened forms data; and (4) 4 interjection data.